Geologic History and Crater Morphology of Asteroid (162173) Ryugu. Issue 8 (29th July 2021) - Cho, Y.; Morota, T.; Kanamaru, M.; Takaki, N.; Yumoto, K.; Ernst, C. M.; Hirabayashi, M.; Barnouin, O. S.; Tatsumi, E.; Otto, K. A.; Schmitz, N.; Wagner, R. J.; et al.
Abstract: Crater morphology and surface age of asteroid (162173) Ryugu are characterized using the high‐resolution images obtained by the Hayabusa2 spacecraft. Our observations reveal that the abundant boulders on and under the surface of the rubble‐pile asteroid affect crater morphology. Most of the craters on Ryugu exhibit well‐defined circular depressions, unlike those observed on asteroid Itokawa. The craters are typically outlined by boulders remaining on the rim. Large craters (diameter > 100 m) host abundant and sometimes unproportionally large boulders on their floors. Small craters (<20 m) are characterized by smooth circular floors distinguishable from the boulder‐rich exterior. Such small craters tend to have dark centers of unclear origin. The correlation between crater size and boulder number density suggests that some processes sort the size of boulders in the shallow (<30 m) subsurface. Furthermore, the crater size‐frequency distributions (CSFDs) of different regions on Ryugu record multiple geologic events, revealing the diverse geologic history on this 1‐km asteroid. Our crater‐counting analyses indicate that the equatorial ridge is the oldest structure of Ryugu and was formed 23–30 Myr ago. Then, Ryugu was partially resurfaced, possibly by the impact that formed the Urashima crater 5–12 Myr ago. Subsequently, a large‐scale resurfacing event formed the western bulge and the fossae 2–9 Myr ago. Following this process, the spin of Ryugu slowed down plausibly due to the YORP effect. The transition of isochrons in a CSFD suggests that Ryugu was decoupled from the main belt and transferred to a near‐Earth orbit 0.2–7 Myr ago. Plain Language Summary: Japan's asteroid explorer Hayabusa2 visited the carbon‐rich, 1‐km asteroid named Ryugu. One of the onboard cameras took many pictures of asteroid's surface. In order to know the history of this asteroid, we estimate the age of different geologic units by counting craters. We also documented how the craters on this asteroid look, to help understand the geology of the carbon‐rich world. We found that the mountain range running along the equator formed 23‐30 million years ago. About 5–12 million years ago, the meteorite impact that formed the biggest crater on this asteroid likely scattered soil around, erasing nearby craters that existed before. Then, about 2–9 million years ago, the western half of this asteroid was wiped out by a large‐scale movement of rocks and pebbles that build this asteroid, because the asteroid was spinning fast and unstable at that time. Then, sometime between 0.2 and 7 million years ago, this asteroid left the home of asteroids located between Mars and Jupiter orbits, and came to the orbit passing near the Earth. During its journey to the near‐Earth orbit, the spin of the asteroid slowed down because of the very weak but effective force by heat radiation from surface rocks. Key Points: Craters on asteroid Ryugu are documented and counted based on the high‐resolution images obtained with Hayabusa2's telescopic camera Crater morphology on Ryugu ranges from distinct >100‐m circular depressions to <10 m smooth texture outlined by boulders Crater chronology reveals multiple resurfacing events on each hemisphere 2–12 Myr ago and Ryugu's departure from the main belt <7 Myr ago